2012
DOI: 10.1590/s0102-695x2012005000002
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening, antinociceptive and anti-inflammatory activities of Chrysopogon zizanioides essential oil

Abstract: Abstract:Chrysopogon zizanioides (L.) Roberty, Poaceae, is a plant widely used in northeast Brazil in folk medicine for the treatment of various pathological conditions, including infl ammatory pain. The present study evaluated the antinociceptive and antiinfl ammatory effects of C. zizanioides essential oil (EO) in rodents. EO was further characterized by GC/MS. The major components of EO were identifi ed as khusimol (19.57%), E-isovalencenol (13.24%), α-vetivone (5.25%), β-vetivone (4.87%) and hydroxy-valenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
1
4
0
1
Order By: Relevance
“…beta eudesmol were identified. Similar findings were reported earlier in the essential oil of C. zizanioides (10)(11)(12). But the methodology followed in this study is simpler and cheaper than other distillation methods followed (13).…”
Section: Discussionsupporting
confidence: 89%
“…beta eudesmol were identified. Similar findings were reported earlier in the essential oil of C. zizanioides (10)(11)(12). But the methodology followed in this study is simpler and cheaper than other distillation methods followed (13).…”
Section: Discussionsupporting
confidence: 89%
“…According to Lima and colleagues [28], an excellent indicator of anti-inflammatory activity of new compounds is the peritoneal cell migration inhibition in acute inflammation models. In the present study, it was verified that F2.0v polysaccharide is be able to inhibit the migration of leukocytes into the mice peritoneal cavity after stimulation with peptone in all tested concentrations (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…It also reduced the number of writhings in a dose-dependent manner but did not display activity on thermal hyperalgesia ( Lee et al, 2019 ). In the study by Lima et al (2012) the EO of Chrysopogon zizanioides L (Roberty, Poaceae) produced antinociception similar to morphine in the acetic acid test, and this effect was partially reversed by naloxone. Moreover, it reduced the licking time in the second phase of the formalin test, but it did not demonstrate any effects in the Hargreaves’ test.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the two items regarding selection bias, no study reported the method of allocation and, even though they conducted baseline measures, none of the studies describe how experimental groups were composed to ensure homogeneity and consistency. Only the study by Lima and collaborators (Lima et al, 2012) in which mice with baseline latencies of more than 10 s, and studies by de Oliveira Júnior and colleagues (de Oliveira Júnior et al, 2017;de Oliveira et al, 2018) of more than 20 s, at the hot-plate were excluded from the experiments.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
See 1 more Smart Citation